The evaluation of the lipid-lowering potential of the fish oil from bangus (Chanos chanos Forsskal) in high-fat diet-induced hyperlipidemia in Sprague Dawley rats - Gonzales, Thea Ruth Frances​
Altered plasma lipids and oxidative stress have been involved in the pathogenesis of many cardiovascular diseases (CVDs). Research has shown that increasing antioxidant intake in subjects with abnormally high lipid levels can attenuate the course of the disease. Fish oil, having been reported to have effects on plasma lipids and oxidative stress, might have the potential to delay the progression of atherosclerotic cardiovascular event (ASCVE). The present study was undertaken to evaluate the lipid-lowering potential of the fish oil from Bangus (Chanos chanos Forsskal) in high-fat diet-induced hyperlipidemia in Sprague Dawley rats. Serum lipid profile (TC, TG, VLDL-, LDL- and HDL-cholesterol), atherogenic indices and serum enzymes (ALT, AST, ALP, LDH, and CK-MB) were examined. The results of the study revealed that the bangus fish oil has good free radical scavenging activity which was measured through the DPPH assay. Administration of the bangus fish oil (5mL/KBW/day) has lipid-lowering effect against hyperlipidemia induced by cholesterol feeding for 28 days in male rats as evidenced by lowering TC, TG, VLDL-, and LDL-cholesterol levels in the treated groups (p<0.05). Furthermore, the bangus fish oil has also been seen to offer mild protection in both the liver and heart from damage in high-fat diet-induced hyperlipidemia as the serum biomarkers for hepatic (ALT, AST, and ALP) and cardiac function (LDH, CK-MB) showed to have reverted back to normal to borderline normal levels (p<0.05). These results suggest that the lipid-lowering ability of the bangus fish oil might be correlated to its ability to scavenge free radical, which may be due to Its LCMUFA and PUFA contents. Furthermore, the results of the assessment of atherogenic indices highlight the relevance of bangus (Chanos chanos Forsskal) in the Filipino diet and advocates the increase of bangus consumption to improve the quality of Filipino diet, decrease the risk of several disorders.